Swedish Bird Survey: Fixed routes (Standardrutterna) - Åke Lindström; Martin Green (Lund University, 2020)
The fixed routes (standardrutterna) are one of several schemes within the Swedish Bird Survey (see below), run by the Department of Biology at Lund University, on behalf of the Swedish Environmental Protection Agency. The fixed routes were initiated in 1996 as a standardized method for detecting and reporting changes in the abundance of birds (since 1996) and mammals (since 2011), and their distributions in Sweden over time.

This is possible due to the routes being distributed across Sweden in such a way that all main habitats are surveyed in a representative manner, and by counting birds and mammals using the same methods, in the same locations, year after year.

The surveys are carried out by volunteer ornithologists.

In this dataset, some information is placed in the table ExtendedMeasurementOrFacts (eMoF), which is part of the Source Archive available to download directly from the dataset’s page here on gbif.org. The Source Archive contains the data exactly as uploaded to gbif (verbatim). Should you choose to download the dataset as GBIF Annotated Archive instead, the data has been interpreted and quality controlled by gbif, but, the data in the eMoF will not be included as the eMoF extension is not yet supported by gbif.
Keywords: Samplingevent; Samplingevent; SAMPLING_EVENT; Biological Sciences; Biologi